2016
DOI: 10.1093/bioinformatics/btw209
|View full text |Cite
|
Sign up to set email alerts
|

Romulus: robust multi-state identification of transcription factor binding sites from DNase-seq data

Abstract: Motivation: Computational prediction of transcription factor (TF) binding sites in the genome remains a challenging task. Here, we present Romulus, a novel computational method for identifying individual TF binding sites from genome sequence information and cell-type–specific experimental data, such as DNase-seq. It combines the strengths of previous approaches, and improves robustness by reducing the number of free parameters in the model by an order of magnitude.Results: We show that Romulus significantly ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Second, the approach proposed here, like any of the other supervised approaches (Natarajan et al ., 2012; Arvey et al ., 2012; Luo and Hartemink, 2012; Kahara and Lahdesmaki, 2015; Kumar and Bucher, 2016; Quang and Xie, 2017; Liu et al ., 2017; Qin and Feng, 2017; Chen et al ., 2017), requires labeled training data for at least one cell type and the TF of interest to make predictions for this TF in another cell type. While the latter limitation is partly overcome by unsupervised approaches (Pique-Regi et al ., 2011; Sher-wood et al ., 2014; Gusmao et al ., 2014; Raj et al ., 2015; Jankowski et al ., 2016), this typically comes at the cost of reduced prediction accuracy (Kahara and Lahdesmaki, 2015; Liu et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the approach proposed here, like any of the other supervised approaches (Natarajan et al ., 2012; Arvey et al ., 2012; Luo and Hartemink, 2012; Kahara and Lahdesmaki, 2015; Kumar and Bucher, 2016; Quang and Xie, 2017; Liu et al ., 2017; Qin and Feng, 2017; Chen et al ., 2017), requires labeled training data for at least one cell type and the TF of interest to make predictions for this TF in another cell type. While the latter limitation is partly overcome by unsupervised approaches (Pique-Regi et al ., 2011; Sher-wood et al ., 2014; Gusmao et al ., 2014; Raj et al ., 2015; Jankowski et al ., 2016), this typically comes at the cost of reduced prediction accuracy (Kahara and Lahdesmaki, 2015; Liu et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…First, motif matches (i.e., predicted binding sites) may be used as prior information and combined with DNase-seq data to distinguish functional from non-functional binding sites (e.g., Pique-Regi et al . (2011); Jankowski et al . (2016); Raj et al .…”
Section: Supplementary Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To solve the problem, emerging studies demonstrated that the genome-wide TF and gene interactions can be accurately predicted using the open chromatin regions identified through DNase-seq (64) or ATAC-seq (65), thus providing an alternative way to establish the TF–lncRNA interactome without ChIP-seq.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, IRF4 and IRF5, which also have GAA-and GAAA-rich motif features similar to that of other IRFs ( Figure S4C), are found positioned in different areas of the network. IRF4, in particular, is localized to the extreme lower left ( Figure S4A; Cluster 1, Chromatin Modifiers) in proximity to pioneer factors and repressors that target large numbers of genes (Jankowski et al, 2016).…”
Section: Network Clustering Differential Gene Expression Analysis Amentioning
confidence: 99%